Ruby's baby brother - White, Kathryn (Kathryn Ivy); Latimer, Miriam (Cambridge, MA : Barefoot Books, 2013)
When her mother brings new baby Leo home, Ruby feels left out until she realizes that she has the important job of being a big sister.
Reading Counts RC
Keywords: Infants -- Juvenile fiction; Siblings -- Juvenile fiction; Stories in rhyme; Babies -- Fiction; Brothers and sisters -- Fiction; African Americans -- Fiction; Romans, nouvelles, etc. pour la jeunesse; Infants -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Siblings; Infants; Family -- Fiction; Brother -- Fiction; Picture books for children; Picture books; Stories in rhyme; Stories in rhyme; Picture books; Stories in rhyme; Fiction; Juvenile works; Stories in rhyme